Beach litter occurrence in sandy littorals: The potential role of urban areas, rivers and beach users in central Italy. (5th November 2016) - Poeta, Gianluca; Conti, Luisa; Malavasi, Marco; Battisti, Corrado; Acosta, Alicia Teresa Rosario
Abstract: Litter washed ashore on the coastline, also called beach litter, constitutes one of the most obvious signs of marine litter pollution. Surveys of beach litter represent a fundamental tool for monitoring pollution in the marine environment and have been used world-wide to classify and quantify marine litter. Identifying the sources of marine and beach litter is, together with education, the prime weapon in combating this type of pollution. This work investigates the impact of three main potential land sources on litter occurrence: urban areas, rivers and beach users. Three sources were analyzed simultaneously on a broad scale (Lazio region, central Italy) using a random sampling design and fitting a generalized linear mixed-effect model. The results show that urban areas are the main drivers for the occurrence of marine litter along central Italy's coastal ecosystems, suggesting that the presence of such litter on Lazio beaches could be effectively reduced by identifying failings in recycling and waste collection procedures and by improving waste processing systems and sewage treatment in urban areas. Graphical abstract: Highlights: We studied beach litter occurrence in central Italy sandy littorals. We investigated the impact of 3 different potential sources of beach litter. Urban areas are the main source of litter in the Central Italian beaches.